Effects of Chronic Physical Activity and of Ultrasound Treatment on Bone Consolidation - Guerino, Marcelo Renato [UNESP]; Luciano, Eliete [UNESP]; Goncalves, Mauro [UNESP]; Leivas, Tomaz Puga (My University, 1999)
The objective of this study was to investigate the effects of ultrasound treatment and physical exercise on the velocity of bone consolidation and resistance to deformation. We performed osteotomy in the upper third of the right tibia of rats. Physical training consisted of swimming 1 h per day with a load of 5% b.w. for 30 days. Therapy with medium-intensity ultrasound was applied daily on the damaged area. Wistar rats were divided into the following groups: osteotomized sedentary animals with no ultrasound treatment (1.OSnUS), osteotomized trained animals with no ultrasound treatment (2.OTnUS), osteotomized sedentary animals with ultrasound treatment (3.OSwUS). and osteotomized trained animals with ultrasound treatment (4.OTwUS). The animals were sacrificed for the following analyses: muscle glycogen, serum alkaline phosphatase at the 5th, 10th, 20th, and 30th days, test of maximum resistance to flexion, rupture flexion and mean tibial rigidity at the 30th day. Muscle glycogen was increased at the 20th day: alkaline phosphatase was elevated at the 5th and 20th days in groups 3.OSwUS and 4.OTwUS. and decreased at the 10th day. Groups1.OSnUS and 2.OTnUS did not show significant variations. In the mechanical resistance tests, we noted that ultrasound therapy and the association of physical activity used in the present study showed significant differences in bone resistance and bone rigidity after 30 days of treatment. These facts suggest that ultrasound or physical activity, or their combination may accelerate the process of bone tissue repair.
Keywords: alkaline phosphatase; glycogen; animal; animal experiment; blood; bone regeneration; male; mechanical stress; metabolism; osteotomy; physiology; radiation exposure; rat; skeletal muscle; tibia; time; ultrasound therapy; Wistar rat; Alkaline Phosphatase; Animals; Bone Regeneration; Glycogen; Male; Muscle, Skeletal; Osteotomy; Physical Conditioning, Animal; Rats; Rats, Wistar; Stress, Mechanical; Tibia; Time Factors; Ultrasonic Therapy